COMMUNITY-BASED EDUCATION FINANCING MANAGEMENT TRAINING AT AL-MUSHLIH FOUNDATION KARAWANG - Permana, Hinggil; Wahyudin, Undang Ruslan (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Education financing is often a problem for schools. Such as the difficult source of funds obtained by the school, the foundation, and how to manage finances for the school. In this research, we will discuss socialization activities carried out at SMP Al-Mushlih as a partner. The method of implementation carried out is the method of lectures and questions and answers conducted at the Al-Mushlih Foundation while still observing health protocols. The chairman of the Al-Mushlih Foundation who has responsibilities related to obtaining funds, one of his efforts is to hold entrepreneurs around the school to increase the institution's finances apart from relying on assistance from the government. The conclusion obtained from this socialization activity is the success in attracting partners and the wider community to participate in a series of online events and discussions that can make partners and the wider community one step ahead to gain new knowledge about Community-Based Education Financing Management in Karawang Regency.